Conflitos discursivos e seu consumo na cultura do cancelamento: o caso Karol Conká - Ramos, Kely Priscila Barbosa (2023)
Considering present social dynamics regarding the centrality of the reputation aspect of the contemporary subject, this research aims to understand how the discourses in the practice of the cancel culture are conflicted. Therefore, the investigation is sustained by a bibliographical review of the emergence of the cancel culture, having as an object of analysis the case of the Brazilian singer Karol Conká being canceled in February 2021 in Brazil. This research investigates the logic of production of the communicational conflicts of this cultural practice through a reflexive theorization about cyberculture supported by authors such as Pierre Lévy (1999) and Raquel Recuero (2020) to understand more about the environment in which cancel culture arises. In addition, it observes the discursive production on the social network Twitter, which is the main network for manifesting cancellation, with the support of authors such as Dominique Maingueneau (2015) and Patrick Charaudeau (2019). This research also addresses aspects of the subject's centrality today, such as how their social capital is formed and how the call for the consumption of cancellation speeches is carried out, based on the theoretical view of media and cultural consumption by Nilda Jacks, Mariângela Toaldo (2014) and Néstor García Canclini (1993). Finally, our investigation results in the discursive categories that build this particular case, allowing us to identify that legal, moral, and sentimental issues are the primary pillars of this type of cultural practice that brings discursive conflicts to the extent of disagreement with other social groups about specific ideas and collective thoughts of today's society.